Drought stress amelioration in tomato (Solanum lycopersicum L.) seedlings by biostimulant as regenerative agent - Turan, Metin; Ekinci, Melek; Argin, Sanem; Brinza, Mihail; Yildirim, Ertan (Frontiers in Plant Science, 2023)
Drought adversely affects many physiological and biochemical events of crops. This research was conducted to investigate the possible effects of biostimulants containing plant growth-promoting rhizobacteria (PGPR) on plant growth parameters, chlorophyll content, membrane permeability (MP), leaf relative water content (LRWC), hydrogen peroxide (H2O2), proline, malondialdehyde (MDA), hormone content, and antioxidant enzymes (catalase (CAT), peroxidase (POD), and superoxide dismutase (SOD)) activity of tomato (Solanum lycopersicum L.) seedlings under different irrigation levels. This study was carried out under controlled greenhouse conditions with two irrigation levels (D0: 100% of field capacity and D1: 50% of field capacity) and three biostimulant doses (B0: 0, B1: 4 L ha-1, and B2: 6 L ha-1). The results of the study show that drought stress negatively influenced the growth and physiological characteristics of tomato seedlings while biostimulant applications ameliorated these parameters. Water deficit conditions (50% of field capacity) caused decrease in indole acetic acid (IAA), gibberellic acid (GA), salicylic acid (SA), cytokine, zeatin, and jasmonic acid content of tomato seedlings by ratios of 83%, 93%, 82%, 89%, 50%, and 57%, respectively, and shoot fresh weight, root fresh weight, shoot dry weight, root dry weight, plant height, stem diameter, and leaf area decreased by 43%, 19%, 39%, 29%, 20%, 18%, and 50%, respectively, compared to the control (B0D0). In addition, 21%, 16%, 21%, and 17% reductions occurred in LRWC, chlorophyll a, chlorophyll b, and total chlorophyll contents with drought compared to the control, respectively. Biostimulant applications restored the plant growth, and the most effective dose was 4 L ha-1 under drought condition. Amendment of biostimulant into the soil also enhanced organic matter and the total N, P, Ca, and Cu content of the experiment soil. In conclusion, 4 L ha-1 biostimulant amendment might be a promising approach to mitigate the adverse effects of drought stress on tomato.